Pengembangan UMKM di Sentra Wisata Kuliner Karah Melalui Program Revitalisasi - Rochmah, Firly Dwi Ainur; Andarini, Sonja (As-Syirkah: Islamic Economic & Financial Journal, 2024)
Indonesia has currently provided more jobs to reduce the number of unemployed. To reduce the increasing unemployment rate, it is necessary to improve the quality of human resources, especially through empowerment. The city of Surabaya supports underprivileged street vendors by opening a culinary tourism center. The aim of this research is to describe the development of micro, small and medium enterprises (MSMEs) through the Karah Culinary Tourism Center revitalization program. The method used is qualitative with a descriptive approach to study the development of MSMEs through revitalization programs. The survey results show that the Government has implemented a policy to build and provide space for street vendors at the Karah Culinary Tourism Center.